A Wideband Magnetic Frequency Up‐Converter Energy Harvester. Issue 6 (5th March 2021) - Fakeih, Esraa; Almansouri, Abdullah S.; Kosel, Jürgen; Younis, Mohammad I.; Salama, Khaled N.
Abstract : Many sensor applications require small and noninvasive methods of powering, such as marine animal tracking and implantable healthcare monitoring. In such cases, energy harvesting is a viable solution. Vibrational energy harvesting is abundantly available in the environment. These vibrations usually are low in frequency and amplitude. Conventional vibrational harvesters convert the environmental vibrations into electrical signals; however, they suffer from low‐voltage outputs and narrow bandwidths, limiting the harvesting to a small range of frequencies. Herein, a new mechanical harvester is introduced using a magnetic frequency up‐converter. It is implemented using attractive‐force magnetic coupling between a soft magnet and a permanent magnet to convert low‐frequency vibrations into high‐frequency pulses. Combined with a piezoelectric generator, the harvester generates a high output voltage for an extended bandwidth of operation. The proposed harvester shows a 50.15% increase in output voltage at the resonant frequency (12.2 Hz), resulting in 14.79 V at 1.0 g, with a maximum peak voltage of 16.28 V. The bandwidth of operation ranges from 10.77 to 22.16 Hz (11.39 Hz), which when compared with a single‐beam harvester shows an increase of 3250% in the bandwidth, where the average power is greater for 92.56% of this bandwidth. Abstract : A magnetic vibrational energy harvester is proposed. A permanent magnet is attached to a low‐frequency (LF) beam, attracting a soft‐magnet high‐frequency (HF) beam. The system converts LF ambient vibrations to HF pulses and with an added piezoelectric material generates an amplified output voltage. The system has an extended bandwidth of operation, all while operating at LF and low‐acceleration conditions.